Driving after concussion: is it safe to drive after symptoms resolve?. Issue 11 (25th May 2017) - Schmidt, Julianne D; Devos, Hannes; Hoffman, Nicole L; Ranchet, Maud; Akinwuntan, Abiodun E; Miller, L Stephen
Abstract : Objective: To compare simulated driving performance between concussed and control participants. Design: Cross-sectional. Setting: Laboratory. Subjects: Fourteen concussed participants and 14 non-concussed age and driving experience matched controls with no neurological disorders, medications causing drowsiness, or heavy drugs/alcohol use (Age: 20.3years, 95%CI:19.9, 20.7). Intervention: Participants completed a 7.6 minute, 20.5km driving simulation task containing curves, crosswalks, accidents, rural/urban areas, pedestrians, overtaking, and evasion. Concussed participants completed driving simulation within 48 hours of becoming asymptomatic (15.9 days post-concussion, 95%CI: 10.7, 21.0) and were deemed clinically recovered by a medical professional using a multifaceted concussion evaluation. Outcome measures: We compared total number of accidents, tickets, and lane excursions between groups.We also comparedaverage velocity (km/hr), standard deviation of velocity, lateral lane position (m), and lateral lane position standard deviation throughout simulation subsections. One-way ANOVAs were used (α=0.05). Results: Concussed participants committed more frequent lane excursions compared to controls (concussed: 10.9, 95%CI:8.3, 13.5; controls: 7.4, 95%CI:6.0, 8.8; p=0.02). Concussed participants exhibited greater lateral lane position standard deviation compared to controls during the first (concussed: 1.1m, 95%CI: 0.8, 1.5; controls: 0.7m, 95%CI:0.6, 0.9; p=0.02) and final curve (concussed: 1.2m, 95%CI:1.1, 1.3; controls: 1.0m, 95%CI:0.9, 1.1; p=0.04). Conclusions: Despite being considered clinically recovered, concussed participants were less able to centre the vehicle in the lane and entered the shoulder more frequently, especially when navigating curves. A concussion may impair visual, motor, and/or cognitive skills necessary to safely drive. Further research is needed to determine when it is safe to return to driving following concussion. Competing interests: None.